MOTIVASI ORANG TUA MENYEKOLAHKAN ANAKNYA DI LEMBAGA PENDIDIKAN ISLAM DI DESA BATU MERAH KECAMATAN SIRIMAU KOTA AMBON - Mila Sari Selan (IAIN Ambon, 2021)
Abstract The focus of this research is the Motivation of Parents in Sending Their Children to Islamic Education Institutions in Batu Merah Village, Sirimau District, Ambon City. Theproblem formulations in this study are: 1) motivation to send their children to Islamiceducational institutions, 2) factors that affect the motivation of parents to send their childrento Islamic educational institutions. The purpose of this study is to know the motivation to sendtheir children to Islamic educational institutions and know the factors that affect the motivationof parents to send their children to Islamic educational institutions. The type used in thisstudy is qualitative descriptive. The results showed that the motivation of parents in sendingtheir children to Islamic educational institutions is 1) Parents view Islamic educationalinstitutions as the best educational option for children because Islamic educationalinstitutions are education based on Islamic teachings so that it is understood as the mosteffective place to create children's Islamic life compared to public schools, 2) Parents viewIslamic educational institutions as having a good vision for children, 3) parents view islamicinstitutions as having a good vision.Keywords: Parental motivation, Islamic educational institutions Abstrak: Fokus penelitian ini adalah Motivasi Orang Tua Dalam MenyekolahkanAnaknya Di Lembaga Pendidikan Islam Di Desa Batu Merah Kecamatan SirimauKota Ambon. Rumusan masalah dalam penelitian ini adalah: 1) motivasimenyekolahkan anaknya di lembaga pendidikan Islam, 2) faktor-faktor yangmempengaruhi motivasi orang tua menyekolahkan anaknya di lembaga pendidikanIslam. Tujuan dari penelitian ini yaitu mengetahui motivasi menyekolahkan anaknyadi lembaga pendidikan Islam dan mengetahui faktor yang mempengaruhi motivasiorang tua menyekolahkan anaknya di lembaga pendidikan Islam. Tipe yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Hasil penelitianmenunjukkan bahwa motivasi orang tua dalam menyekolahkan anaknya di lembagapendidikan Islam yaitu 1) Orang tua memandang lembaga pendidikan Islam sebagaipilihan pendidikan yang terbaik untuk anak karena lembaga pendidikan Islam adalahpendidikan yang berbasis ajaran agama Islam sehingga dipahami sebagai tempatyang paling efektif untuk menciptakan kehidupan Islami anak dibanding dengansekolah-sekolah umum, 2) Orang tua memandang lembaga pendidikan Islammempunyai visi yang baik untuk anak, 3) orang tua memandang lembaga